Viewing Violence, Mental Illness and Addiction Through a Wise Practices Lens - Wesley-Esquimaux, Cynthia C.; Snowball, Andrew (International Journal of Mental Health and Addiction, 2010)
The progressive approaches First Nations, MeÌtis, and Inuit communities use to address health and wellness concerns are rarely written about or acknowledged in a positive manner. This paper speaks to a concept introduced through the Canadian Aboriginal Aids Network (CAAN) entitled â€œwise practicesâ€. CAAN saw a wise practices model as more useful and inclusive of Aboriginal community practice and knowledge exchange than the current â€œbest practiceâ€ model. In addition, wise practices acknowledge and express the notion of â€œChanging the Face of Aboriginal Canadaâ€, a metaphor frequently used by the senior author of this paper, as a long overdue vehicle for lifting up the collective morale of Aboriginal peoples in Canada. Indigenous peoples worldwide have long articulated an inherent wisdom in developing recovery processes. This natural wisdom has been chronically dismissed and underutilized as a framework for re-building a healthy social construct and worldview. The social and emotional utility of constructing and implementing a â€œwise practicesâ€ healing model based on what are commonly referred to as the Seven Sacred Values, has great potential for addressing violence, mental illness and addictions in Aboriginal communities and can better serve health promotion alongside the western model of â€œbest practices.â€ A wise practices model becomes another, deeply humane way, of expressing and operationalizing the traditional knowledge base of Aboriginal Canada and returns a sense of self-efficacy and social strength to Aboriginal communities.